2004
DOI: 10.1007/s00167-003-0474-4
|View full text |Cite
|
Sign up to set email alerts
|

Full arthroscopic lateral retinacular release with hook knife and quadriceps pressure-pull test: long-term follow-up

Abstract: The most important causes of anterior knee pain include patellofemoral malalignment which causes patella-condyle contact anomalies at the patellofemoral joint, excessive patellar lateral pressure increase, trauma and overuse. In this article, besides presentation of late clinical results of 169 lateral retinacular release cases which were surgically treated between January 1995 and December 2002 with the help of a hook knife from the anterolateral portal due to lateral compression syndrome and patellar maltrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
16
1
Order By: Relevance
“…Prior studies have reported results of ALRR for patellar instability in an adolescent population 31 and ALRR for pain in a general population. 8,9,13,15,32 Roth et al 31 reported a mean 31-point improvement in Lysholm score after ALRR for patellar instability in adolescent athletes, similar to the 35-point improvement in IKDC score seen in the current study. Results of ALRR for pain in the general population have been variable, with some studies reporting low levels (14% to 60%) of "satisfactory" results 13,15 and others demonstrating promising clinical outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Prior studies have reported results of ALRR for patellar instability in an adolescent population 31 and ALRR for pain in a general population. 8,9,13,15,32 Roth et al 31 reported a mean 31-point improvement in Lysholm score after ALRR for patellar instability in adolescent athletes, similar to the 35-point improvement in IKDC score seen in the current study. Results of ALRR for pain in the general population have been variable, with some studies reporting low levels (14% to 60%) of "satisfactory" results 13,15 and others demonstrating promising clinical outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Results of ALRR for pain in the general population have been variable, with some studies reporting low levels (14% to 60%) of "satisfactory" results 13,15 and others demonstrating promising clinical outcomes. 8,9 Calpur et al 8 reported results of ALRR for pain in 80 patients aged 16 to 40 and found a mean 31-point improvement in Lysholm score, and 100% of knees were normal or nearly normal by IKDC objective assessment at long-term follow-up. O'Neill 9 reported results of ALRR for pain in 43 patients aged 13 to 56 and found that 77% of patients had good or excellent Lysholm score at >2 years' follow-up and 93% were able to return to athletic activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For knees demonstrating medial abrasion phenomenon, medial release (Lyu SR, 2008) was performed to relieve the tension and abrasion between the tight, fibrotic and hypertrophied medial plica and the adjacent medial femoral condyle that have been described in previous studies (Lyu SR and Hsu CC, 2006;Lyu SR, 2007;Lyu et al, 2010). On the other hand, in knees demonstrating lateral compression syndrome over patellofemoral joint, percutaneous lateral capsular release that has the benefits of tension release and denervation (Calpur OU et al, 2005;Paulos LE et al, 2008) was added. The immediate effect of ACRFP is to release the strain caused by chronically inflamed soft tissue and to eradicate the hypertrophied synovium that may cause pain in the degenerative knees over the medial compartment and patellofemoral joint.…”
Section: Arthroscopic Cartilage Regeneration Facilitating Procedures (mentioning
confidence: 99%
“…This procedure is performed arthroscopically, and may be accompanied by tightening of the medial structures (medial reefing) [10]. As with all arthroscopic procedures, scarring may be seen in Hoffa's fat pad (Fig.…”
Section: Lateral Patellar Facet Compression Syndromementioning
confidence: 99%